Endoplasmic reticulum stress in adipose tissue augments lipolysis - Bogdanovic, Elena (J Cell Mol Med, 2015)
The endoplasmic reticulum (ER) is an organelle important for protein synthesis and folding, lipid synthesis and Ca(2+) homoeostasis. Consequently, ER stress or dysfunction affects numerous cellular processes and has been implicated as a contributing factor in several pathophysiological conditions. Tunicamycin induces ER stress in various cell types in vitro as well as in vivo. In mice, a hallmark of tunicamycin administration is the development of fatty livers within 24–48 hrs accompanied by hepatic ER stress. We hypothesized that tunicamycin would induce ER stress in adipose tissue that would lead to increased lipolysis and subsequently to fatty infiltration of the liver and hepatomegaly. Our results show that intraperitoneal administration of tunicamycin rapidly induced an ER stress response in adipose tissue that correlated with increased circulating free fatty acids (FFAs) and glycerol along with decreased adipose tissue mass and lipid droplet size. Furthermore, we found that in addition to fatty infiltration of the liver as well as hepatomegaly, lipid accumulation was also present in the heart, skeletal muscle and kidney. To corroborate our findings to a clinical setting, we examined adipose tissue from burned patients where increases in lipolysis and the development of fatty livers have been well documented. We found that burned patients displayed significant ER stress within adipose tissue and that ER stress augments lipolysis in cultured human adipocytes. Our results indicate a possible role for ER stress induced lipolysis in adipose tissue as an underlying mechanism contributing to increases in circulating FFAs and fatty infiltration into other organs.